Brain metastases in patients with neuroendocrine neoplasms: risk factors and outcome - Krug, Sebastian (BMC Cancer, 2019)
BACKGROUND: Brain metastases (BM) are rarely reported in patients with neuroendocrine carcinoma (NEC) of non-lung origin and neuroendocrine tumors (NET) of the gastroenteropancreatic (GEP) or bronchopulmonary system. However, symptomatic brain metastases are associated with dismal prognosis, so early detection and treatment could be advisable. METHODS: We retrospectively analyzed 51 patients with GEP-NEN and bronchopulmonary NEN excluding small cell lung cancer. All patients were treated at the University Hospital Marburg and Halle (Saale) between 2000 and 2017. The median overall survival (mOS) and mOS after diagnosis of brain metastases (BM) were calculated using Kaplan-Meier analysis. Risk factors for poor prognosis were evaluated using univariate and multivariate Cox regression method. RESULTS: Overall, 51 patients with a median age of 58 years presented BM. Lung (n = 23, 45.1%) was the most frequent primary localization. Most patients had NEC (n = 31, 60.8%), including 26 carcinomas (51%) with Ki-67 indices > 55%. Singular BM were present in 16 patients (31.4%), but 21 patients (41.2%) had multiple lesions. Overall, the median period from first diagnosis of the tumor disease up to diagnosis of brain metastasis was 5.0 months. Palliative radiation was the most common therapy (n = 31, 60.8%). Median OS after initial diagnosis and diagnosis of BM was 23.0 and 11.0 months, respectively. Univariate and multivariate analysis for prognostic indicators depicted differentiation (NEC HR 4.2, 95% CI 1.1–16.1) and age (≥60 HR 3.0, 95% CI 1.2–7.5) as markers for poor outcome. CONCLUSIONS: Overall, the risk for symptomatic brain metastases is low in GEP-NEN and bronchopulmonary NEN patients. Age above 60 and poor tumor differentiation may deteriorate the overall survival. Therefore, screening for brain metastases could be advisable in NEC patients.